Blocking NS3-NS4B interaction inhibits dengue virus in non-human primates - Goethals, Olivia; Kaptein, Suzanne J. F.; Kesteleyn, Bart; Bonfanti, Jean-François; Van Wesenbeeck, Liesbeth; Bardiot, Dorothée; Verschoor, Ernst J.; Verstrepen, Babs E.; Fagrouch, Zahra; Putnak, J. Robert; Kiemel, Dominik; Ackaert, Oliver; et al. (Nature, 2023)
Dengue is a major health threat and the number of symptomatic infections caused by the four dengue serotypes is estimated to be 96 million1 with annually around 10,000 deaths2. However, no antiviral drugs are available for the treatment or prophylaxis of dengue. We recently described the interaction between non-structural proteins NS3 and NS4B as a promising target for the development of pan-serotype dengue virus (DENV) inhibitors3. Here we present JNJ-1802—a highly potent DENV inhibitor that blocks the NS3-NS4B interaction within the viral replication complex. JNJ-1802 exerts picomolar to low nanomolar in vitro antiviral activity, a high barrier to resistance and potent in vivo efficacy in mice against infection with any of the four DENV serotypes. Finally, we demonstrate that the small-molecule inhibitor JNJ-1802 is highly effective against viral infection with DENV-1 or DENV-2 in non-human primates. JNJ-1802 has successfully completed a phase I first-in-human clinical study in healthy volunteers and was found to be safe and well tolerated4. These findings support the further clinical development of JNJ-1802, a first-in-class antiviral agent against dengue, which is now progressing in clinical studies for the prevention and treatment of dengue.
Gesehen am 23.05.2023